(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to identify factors associated with adherence to oral bisphosphonate therapy in patients aged ≥60 years with osteoporosis, using the Vietnamese version of the MARS-5 scale, to inform strategies for improving treatment effectiveness in Vietnam. Methods: A cross-sectional study was conducted at the University Medical Center Ho Chi Minh City between November 2022 and April 2023, enrolling 172 outpatients aged ≥60 years diagnosed with osteoporosis and receiving oral bisphosphonates. Medication adherence was assessed using the validated Vietnamese version of the MARS-5 questionnaire. Demographic, clinical, and knowledge-related variables were collected. Univariate and multivariate logistic regression analyses were performed to identify independent factors associated with adherence. Results: Among 172 patients (149 females, 23 males; mean age 68.7 ± 6.9 years), multivariate analysis revealed three independent factors significantly associated with adherence: treatment duration ≥12 months (p < 0.001), lack of knowledge about the benefits of medication (p = 0.017), and lack of awareness of fracture complications of osteoporosis (p = 0.022). Conclusion: Adherence to oral bisphosphonate therapy in older adults is influenced by treatment duration and patient knowledge regarding medication benefits and fracture complications. Regular screening using the MARS-5 scale and enhanced patient education are essential to improve adherence and prevent osteoporotic fractures.